2013
DOI: 10.1038/srep02185
|View full text |Cite
|
Sign up to set email alerts
|

Capillary flow of amorphous metal for high performance electrode

Abstract: Metallic glass (MG) assists electrical contact of screen-printed silver electrodes and leads to comparable electrode performance to that of electroplated electrodes. For high electrode performance, MG needs to be infiltrated into nanometer-scale cavities between Ag particles and reacts with them. Here, we show that the MG in the supercooled state can fill the gap between Ag particles within a remarkably short time due to capillary effect. The flow behavior of the MG is revealed by computational fluid dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For example, some amorphous alloys can be blow-molded into various shapes due to their thermoplastic formability in SCLR [3,4]. In addition, we previously exploited the liquid-like behavior of Al-based amorphous alloys in SCLR to develop Ag paste for solar cells [5][6][7]. The Ag paste with Al85Y8Ni5Co2 (AYNC) exhibited better electrical properties than those with Al85.4Y10Ni5.5 (AYN) and Al86Y6Ni4.5Co2La1.5 (AYNCL).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some amorphous alloys can be blow-molded into various shapes due to their thermoplastic formability in SCLR [3,4]. In addition, we previously exploited the liquid-like behavior of Al-based amorphous alloys in SCLR to develop Ag paste for solar cells [5][6][7]. The Ag paste with Al85Y8Ni5Co2 (AYNC) exhibited better electrical properties than those with Al85.4Y10Ni5.5 (AYN) and Al86Y6Ni4.5Co2La1.5 (AYNCL).…”
Section: Introductionmentioning
confidence: 99%
“…Yttrium in HP heatresistant steels increased the fragmentation of primary carbides obstructing the continued growth of creep cracks [16,17]. Cerium in 27Cr-7Ni duplex steel retards the precipitation of sigma phase during annealing at the temperature of 600-1000 °C after solid-solution heat treatment, which inhibited the degradation of mechanical properties [18]. As a result, it is considered to be feasible to improve the creep properties of 316LN steel by RE addition.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Based on such exotic properties, it has been reported that metallic glasses can be used as functional materials for binding 14 and nano/micro imprinting. 15 As a result, metallic glasses have been successfully applied for electrode for solar cell 16 and catalyst for fuel cell. 10,[17][18][19] One of the prerequisites for such applications is that metallic glasses should have a wider SCL region, which can provide a larger processing window for fabrication.…”
mentioning
confidence: 99%